PERAN KINERJA BANK DALAM PENGARUH MAKRO EKONOMI TERHADAP RETURN SAHAM - Fransiska Dewi, Putu Yesi; Wiksuana, I Gusti Bagus; Artini, luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
The banking sector is an attractive sector for investors to receive a return.  The ambition of this investigation is to appreciate the character of the bank's performance in theinteraction of  macro-economic and stock returns in banking sector BEI. 23 banking companies used to be sample using purposive method with the provisions of banking companies during the 2010-2014 period did not suffer losses.  The role of mediation was tested using path analysis and Sobel test This investigation resulted in the depreciation of macroeconomic causes decreased stock return and increase the good performance of banks led to an increase in stock return. Instead bank performance positively and significantly influenced by the macro economy. Sobel test proved that the role of performance of the bank as a partial mediation in the relationship of macroeconomic influence to stock return of the banking sector in the BEI.
Keywords: Stocks Return; Macro Economics; Bank Performance ?